PENUMBUHAN BUDAYA LITERASI DENGAN PENERAPAN ILMU KETERAMPILAN BERBAHASA (MEMBACA DAN MENULIS) - Mursalim, Mursalim (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
Indonesia has the wealth and diversity of the nation as the population of approximately 240 million, ethnic and regional languages, religions, diverse cultures, diverse customs and customs, and a wide variety of flora and fauna that all these things are very necessary to be understood and known by all layers community and built, disclosed, communicated both orally and in writing. In order for the wealth and diversity of such a nation to be known and understood as well as possible by all citizens of Indonesia, then every citizen is also expected to no longer experience illiteracy, or otherwise all literate. Therefore, the author of this paper will explain the growth of literacy culture with the science of reading and writing language skills. The purpose of this paper is to provide information to the reader community about the process of cultural growth of literacy with the application of the science of reading and writing language skills. The things that will be presented in this paper are (a) understanding of literacy and cultural literacy, (b) the growth of literacy culture, (c) understanding of language skills, (d) applying the science of writing language skills, and (e) read. It can be concluded that literacy is literacy, namely the ability to write and read. Then, the literacy culture is meant to do the habit of thinking followed by a process of reading, writing, in the end, what is done in a process of the activity will create the work. Keywords: culture of literacy, language skills, reading, writing